Land registration and title security in the digital age : new horizons for Torrens - New Horizons for Torrens: Current reforms, emerging issues (Conference) (2018 : University of Auckland, Faculty of Law); Grinlinton, David P. (David Paul), 1956-; Thomas, Rod, 1957-; University of Auckland. Faculty of Law (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book examines the current state of, and emerging issues in relation to, the Torrens and other systems of land registration, and the process of automation of land registration systems in jurisdictions where this is occurring worldwide. It analyses the impacts of advances in digital technology in this area and includes contributions from of a number of experts and leaders in this subject from a number of jurisdictions. While it has an Australasian bias, there are important chapters outlining current challenges and developments in Scotland, England and Wales, Ireland, and the Netherlands. The book will be relevant to those engaged in land registration and conveyancing processes, including, but not limited to, property law practitioners and conveyancers, academics in this field, government and public policy experts, law and property students, and IT and IP experts, especially those working on developing automated land registration systems"--
Foreword / D. W. MCMORLAND -- Introduction / DAVID GRINLINTON AND ROD THOMAS -- Title Guarantee or Title Indefeasibility? / MARTIN DIXON -- Fraud and Torrens / WILLIAM GUMMOW -- In Personam Claims : Developments and Thoughts / FIONA BURNS -- Indefeasibility of Title : Law Reform in Scotland and New Zealand / KENNETH G. C. REID -- Recent Developments in the Torrens System in Australia / BRENDAN EDGEWORTH -- Reform of the New Zealand Land Transfer Act 2017 / PETER BLANCHARD -- The New Fraud Test and Manifest Injustice / NEIL CAMPBELL AND ROD THOMAS -- Knocking at the Compensation Door : What Might a Deprived Owner Expect Under the Land Transfer Act 2017? / ELIZABETH TOOMEY -- The Registrar's Powers in the Digital Age / DAVID GRINLINTON -- Making Personal Obligations Binding : Covenants in Gross and incumbrances Under New Zealand's New Land Transfer Act / THOMAS GIBBONS -- Automation, the Land Registration Act (England and Wales) and the Future / -- NICK HOPKINS -- Automation of a Torrens Register : An Australian Perspective / SHARON CHRISTENSEN -- The Development and Current Position of Electronic Conveyancing in Ireland / SANDRA MURPHY -- Automation of the New Zealand Torrens Register : Practitioner Abuse, Risk and Liability / ROD THOMAS -- Are Land Registers Becoming Online Intermediary Platforms of Land Data? / SJEF VAN ERP -- Privatisation, the Consensus Algorithms of Blockchains, and Land Titling in Australia : Where Are We Now, and Where Are We Going? / LYNDEN GRIGGS AND ROUHSHI LOW -- Judicial Interpretation of Torrens Registered Documents / BEN FRANCE-HUDSON -- Indigenous Land Rights and Land Registration Systems : Māori and the Land Transfer Act 2017 / LAYNE HARVEY -- Managing Property Law Risk : The Role of Private Insurance / JONATHAN FLAWS -- Land Registration in England & Wales : Problems, Solutions and Missed Opportunities / MARTIN DIXON AND EMMA LEES.
Includes index.
Includes papers presented at a conference "New Horizons for Torrens: Current reforms, emerging issues" held in August 2018 the Auckland University Law School"--ECIP introduction.
OCLC-licensed vendor bibliographic record.
Keywords: Land titles -- Registration and transfer -- Technological innovations -- Congresses; Torrens system -- Technological innovations -- Congresses; LAW / General; LAW / Commercial / General; LAW / Land Use